EKSPRESI AMBISI DALAM NOVEL A STRANGER IN THE MIRROR KARYA SIDNEY SHELDON - Dado, Prawito; Wantasen, Isnawati L.; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTThis research is entitled â€œAmbisi dalam Novel A Stranger In The Mirror Karya Sidney Sheldonâ€ as a requirement to accomplish undergraduate at Faculty of Humanities Sam Ratulangi University Manado. The study aims to determine two main characters names Toby Temple and Jill Castle, on their ambition to achieve a dream to become superstar in Hollywood. This study used psychologycal approach by Alfred Adler theory as the main theory to identify the ambition in the novel. The writer also used Robert Stanton theory to anylized the characters. The method used in this research is descriptive by using intrinsic and extrinsic approach to identify, describe and analyze the ambition in the novel A Stranger in the Mirror. The result shows that Toby and Jill are characters who have a strong determination, they strive to get their dreams. their ambition arises because of impulse factors from within themselves and the environment. External factors such as parents, environment and condition.Keyword : Ambition,,protagonist, A Strnger in the Mirror, Sidney Sheldon, psychology.